Definitions of intradialytic hypotension. Issue 6 (9th July 2017) - Assimon, Magdalene M.; Flythe, Jennifer E.
Abstract: Intradialytic hypotension (IDH) is a common and often distressful complication of hemodialysis. However, despite its clinical significance, there is no consensus, evidence‐based medical definition for the condition. Over the years, numerous definitions have been implemented in both the clinical and research settings. Definition inconsistencies have hindered data synthesis and the development of evidence‐based guidelines for the prevention and treatment of IDH, as well as prevented accurate estimation of the population burden of IDH and patient risk assessment. Most existing IDH definitions are comprised of one or more of the following components: (1) intradialytic BP criteria (requisite BP declines or minimum BP thresholds), (2) the provision of interventions aimed at restoring effective arterial volume, and/or (3) patient‐reported symptoms. Remarkably, there are insufficient data to inform IDH definition construction, and it remains unknown if a single, universal definition can adequately capture the condition across patient subgroups, and in clinical and research settings.